La acción directa frente al incumplimiento entre partes integrantes de un grupo de contratos conexos - Olazabal Tamayo, Luis Anibal (2023)
The purpose of this investigation is to answer the following question: Is it possible to admit the use of the direct action for contractual connection in Peru? In this line, this paper will focus on analyzing whether a creditor -part of a group of related contracts- can exercise against a debtor -part of the same group of contracts- the contractual remedies derived from the breach of the latter, even if there is no contract between them. In order to do so, the origin of the contractual connection as a legal concept and its development in comparative law will be discussed. Subsequently, the nature of the direct action, its characteristics and scope will be analyzed in depth. Then, I will review the way in which the contractual connection has been approached in Peru by the doctrine and jurisprudence, as well as its indirect recognition at the regulatory level. Finally, on the basis of the aforementioned development, I will determine the feasibility of recognizing the use of the direct action against the breach of the parties of a group of related contracts, according to the current regulation of the Peruvian Civil Code. This analysis will be accompanied by an evaluation of: (i) whether it is necessary to amend the Civil Code in order to allow the application of this figure; and, (ii) what would be the practical implications of the use of the direct action in Peru.